Quantitative analysis of cerebrospinal fluid brain derived neurotrophic factor in the patients with multiple sclerosis - Mashayekhi, Farhad; Salehi, Zivar; Jamalzadeh, Hamid Reza (Acta Medica, 2012)
Multiple sclerosis (MS) is the most common cause of nontraumatic neurological disability in Europe and North America. Growth factor expression could participate in the repair process of the demyelinating disease. Among growth factors, brain derived neurotrophic factors (BDNF) has been demonstrated to play an important role in neuronal and axonal survival. In the central nervous system (CNS ), neurons are the main source of BDNF. Another potential source are activated astrocytes, which are present in inflamed areas in the CNS as shown in MS. In this study, total protein concentration (TPC) and BDNF levels in the cerebrospinal fluid (CS F) samples from the patients with MS (n = 48) and control subjects (n = 53) were measured using a Bio-Rad protein assay and enzyme linked immunosorbent assay (ELISA). No significant change in the CS F TPC of patients with MS was seen as compared to normal CS F. The presence of BDNF in the CS F samples was shown by Western blot. Using ELISA , it was shown that the level of BDNF in the MS CS F is higher than in normal CS F. It is concluded that BDNF is a constant component of human CS F. Moreover, it could be implicated in the pathophysiology of MS.
Keywords: ženské pohlaví; Female; roztroušená skleróza; Brain-Derived Neurotrophic Factor; Male; lidé; Adult; mužské pohlaví; dospělí; Humans; mozkový neurotrofický faktor; Multiple Sclerosis